Teacher motivational strategies in Saudi university EFL writing classes: a qualitative study - Abdel Latif, Muhammad M. M.; Alghizzi, Talal Musaed; Alshahrani, Tahani Munahi (Frontiers in Psychology, 2025)
Empirically, motivating students to write is an issue yet to be given due research attention. Some previous relevant works have suggested guidelines for motivating writing students, but the studies qualitatively exploring the realities of writing teachers’ use of motivational strategies remain scant. In this study, we investigated Saudi university teachers’ perceptions of their students’ English writing de-motivation symptoms (i.e., signs or indicators) and causes of lack of motivation to write, and the ways they motivate students to write and participate in classroom activities. We explored these issues through using interviews with 33 teachers (17 males and 16 females) who had English writing instruction experiences at five Saudi universities. The 33 teachers identified seven main symptoms of students’ writing de-motivation (procrastinating assignment submission, engaging rarely in classroom activities, showing writing apprehension, copying others’ writing, skipping classes, perceiving writing value negatively, and experiencing writing block), and they referred to five causes of it (students’ poor language and writing ability, uninteresting topics, ineffective teaching, previous poor experiences, and the cognitive nature of writing). The teachers also reported using eight main motivational strategies in their English writing classes. For these teachers, class size is a very influential factor in their use of motivational strategies. The results generally suggest that writing motivation is yet to be given more attention in Saudi university English writing classes. The study provides the following recommendations: fostering teacher motivation literacy, activating the use of motivational strategies in writing classes, and minimizing class size.